Effect of cigarette smoke extract and electronic cigarette vapour extract on the production of cytokines and chemokines in human airway smooth muscle cells - Alshehri, Wael (2019)
Introduction:Chronic obstructive pulmonary disease (COPD) is characterised by an inflammatory response in the airways to inhaled substances like cigarette smoke. It is known that cigarette smoke extract (CSE) stimulates the production of a number of inflammatory cytokines and chemokines in human airway smooth muscle cells (HASMCs). E-cigarettes are used to aid smoking cessation, but they may also have pro-inflammatory effects. The effect of e-cigarette vapour extract (ECVE) on the production of cytokines and chemokines in HASMCs is unknown. The transcription factor NF-κB regulates immune functions and serves as a mediator of inflammatory responses. It is widely implicated in cigarette smoke-induced airway inflammation. We aim to compare the effect of CSE and ECVE on the production of inflammatory cytokines and chemokines in HASMCS, and investigate whether NF-κB is involved in mediating CSE- and ECVE-induce cytokines and chemokines.